Pengaruh Tipe Industri, Ukuran Perusahaan, dan Kepemilikan Manajerial terhadap Tingkat Pengungkapan Tanggung Jawab Sosial - Harsono, Lindawati; Handoko, Jessica; Fransisca, Ika (Widya Mandala Surabaya Catholic University, 2012)
Since 2007, Iimited companies in Indonesia have responsibility to implement corporate social responsibility as stipulated in the law No. 40/ 2007 regarding the limited companies. Social responsibility which has been implemented will be disclosed o ne way of disclosure is through sustainability report. This study was conducted to examine the influence of type of industry, firm size and managerial ownership on the level of corporate social responsibility disclosure, Samples of this research consist of 18 companies which joined Indonesia Sustainability Reporting Awards in 2008-2010a and published sustainability reports. The results of this study indicate that individually, type of industry variable and company size variable are not significantly influence on the level of social responsibility disclosure. Individually, managerial ownership variable is negatively influence on the level of social responsibility disclosure.